An Assessment of Maximal Isometric Hand Grip Strength and Upper Body Explosive Strength and Endurance in Various Ball Sports - Md Hamidur Rahman; J. P. Sharma (Physical Education Theory and Methodology, 2023)
Background. Playing with the ball and using hand-arm strength and power are very crucial for ball game players. It takes arm force and endurance, as well as isometric hand grip strength, to accomplish ball-game skills.